Formação docente : saberes e práticas nos anos iniciais do ensino fundamental - BONES, Jaquelini (2019)
This study seeks to reflect how the teachers of the initial years of elementary education mobilize and articulate the different types of didactic knowledge in their pedagogical work in a public school in Altamira-PA. As a research problem, we discussed the following: What conceptions about didactics and their pedagogical tendencies underlie the work of the teachers? How do the teachers apply the teaching methodologies / strategies learned in their initial formation? What extent do the working conditions offered to teachers imply their performance in their pedagogical work? This study has as main objective to analyze the pedagogical practices of the teachers of the 3 rd and 4 th levels of elementary education in the public network in Altamira-Pa. This is a qualitative research conducted through interviews with semi-structured questions addressed to two teachers, one from the 3rd and the other from the 4th level of elementary education at a public school of the municipal network in AltamiraPará. We analyze teaching practices, through the observations and data collected through interviews, we realized that the teachers understand the didactic actions as important elements to the learning process from a structured planning, articulated to the methodologies / strategies, which are understood as classroom domain and content to be taught, to pass the content to the student, and to reprimand him it is necessary. Regarding the working conditions, the teachers were in favor of doing pedagogical, because there are good ways for the teaching and learning process to the student.